Social determinants of vaccine hesitancy among the Lebanese parents: A cross-sectional Study - Reem Awad; Mohamad Rahal; Anna-Maria Henieneh; Pascale Salameh; Robin Farah; Michele Cherfane; Reham Kotb; Diana Nakhoul; Rêve Khadaj; Nayla Habib; Katia Iskandar (PLoS ONE, 2026)
Background Vaccines are vital in preventing infectious diseases and saving millions of lives globally. However, the rise of vaccine hesitancy has hindered adequate vaccination coverage, particularly among children. This study explores the social determinants influencing childhood vaccine hesitancy among a sample of Lebanese parents, focusing on how individuals are born, grow, live, and work. Methods A cross-sectional study was conducted using a self-administered questionnaire that gathered socio-demographic characteristics, factors influencing childhood vaccination, and social determinants of health (SDOH). Vaccine hesitancy was measured using a 23-item scale with two subscales (hesitancy and acceptance/trust) rated on a 5-point Likert scale. SDOH included socioeconomic status), Vaccine Health Literacy, Daily Spiritual Experience Scale, and Discrimination in Medical Settings Scale. Data were analyzed using bivariate tests and multivariable linear regression with vaccine hesitancy as the dependent variable. Results A total of 251 participants completed the survey. The mean parental age was 34.94 ± 8.69 years, with 55.8% being female, and the mean child age was 21.35 ± 11.53 months (range: 0–36 months). Higher vaccine hesitancy was observed among individuals reporting higher discrimination in medical settings (Beta = 0.752, p < 0.001), stronger religious beliefs (Beta = 0.866, p < 0.001), and lower SES (Beta = 0.265, p < 0.001). Conversely, higher vaccine literacy (Beta = 0.216, p = 0.035) and a health education background (Beta = 6.262, p = 0.011) were associated with lower hesitancy. Conclusion This study highlights key social determinants of vaccine hesitancy among a sample of Lebanese parents, emphasizing the role of medical discrimination, religious beliefs, and socioeconomic status. Improving vaccine literacy and health education, particularly in vulnerable populations, is crucial to reducing hesitancy. Addressing discrimination in healthcare settings and fostering trust in the medical system are also essential.